A systematic review of technological reporting and support services for women victims of domestic violence - Marçal, Geovanna Kerolyn Goncalves (Seven Editora, 2023)
The present work aims to identify how the security technology search service is directed, as well as a security technology search service, investigating actions and seeking data security, data storage, and retrieval. He delved deeper into relating the general data protection law to security, privacy, and protection issues. In addition to understanding how the demand for concepts works with the reality of society. The technique used for data collection was a way of determining in stages about professional technology and social relationships. The results show that most monitoring agents choose to use technology as a form of intervention for complaints and queries. We understand that society's greater access to society takes place through virtual applications, which are a fundamental technological point in technological advances in all concepts, from science to social issues, and technological advances. There was a need to change the paradigm that society needs to adapt to technology and does not show otherwise. DOI:https://doi.org/10.56238/alookdevelopv1-019